2018
DOI: 10.1002/jgh3.12053
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Helicobacter pylori in the gastric cardia: A comparison between the UFT300 and CLO tests

Abstract: Background and aimTo assess the detection rates of Helicobacter pylori colonization in the gastric cardia with two commercial kits of rapid urease test: 5 min UFT300 and 24 h CLO test in H. pylori‐infected patients.MethodsEighty consecutive dyspeptic patients with confirmed H. pylori infection (serology and 13C‐urea breath test) were prospectively studied. During endoscopy, tissue samples using separate biopsy forceps from the cardia were taken for the UFT300 and CLO tests. The results of the UFT300 were read … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Concerning the endoscopic findings, the crater of peptic ulcer and the inflammation of cardia might influence the eradication rate of ILTHPI due to endoscopic difficult locations for the procedures of ILTHPI including the irrigation of mucus and the application of medicaments. In addition, endoscopic hyperemic change and positive UFT300 of gastric cardia may indicate a higher bacterial load in the cardia [36], leading to failure of ILTHPI. Our study showed that the eradication rate of ILTHPI was not influenced by the presence of peptic ulcer, endoscopic hyperemic change of gastric cardia, and positive UFT300 of gastric cardia.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the endoscopic findings, the crater of peptic ulcer and the inflammation of cardia might influence the eradication rate of ILTHPI due to endoscopic difficult locations for the procedures of ILTHPI including the irrigation of mucus and the application of medicaments. In addition, endoscopic hyperemic change and positive UFT300 of gastric cardia may indicate a higher bacterial load in the cardia [36], leading to failure of ILTHPI. Our study showed that the eradication rate of ILTHPI was not influenced by the presence of peptic ulcer, endoscopic hyperemic change of gastric cardia, and positive UFT300 of gastric cardia.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent H. pylori colonization resulting in subsequent chronic inflammation of cardia has been established in many studies. The rate of colonization detected by rapid urease test in gastric cardia was 90% in H. pylori -infected patients [ 6 ], and was also significantly higher in patients with cardiac cancer (81.5%) and gastric carditis (80.1%) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the cardia in Hp pathogenesis remains largely understudied. Some studies have noted that the gastric cardia was one of the most consistently colonized regions of the stomach in Hp-infected patients, as determined endoscopically ( Genta et al, 1994a ; Liao et al, 2018 ). It remains to be seen whether the cardia indeed represents a preferential site for initial Hp colonization, like the corpus-antrum transition.…”
Section: Introductionmentioning
confidence: 99%